Rat boredom-like behaviour in a monotonous versus a varied foraging task: effects of sensory variation - Charlotte C. Burn; Ka Ho Timothy Ng; Matthew O. Parker (Animal Cognition)
Abstract Evidence increasingly reveals that non-human animals in monotonous situations can show boredom-like states, distinctively manifesting as increases in both arousal-seeking, restless behaviour and low arousal, drowsy behaviour. However, task related boredom has been little investigated in animals, but could have implications for animal training efficacy, for animal welfare, and for modelling human task fatigue. We investigated whether varied sensory stimuli helped prevent boredom-like behaviour in a repetitive foraging scenario, compared with a monotonous equivalent. In a cross-over design, 20 rats searched pairs of containers for a small reward hidden within a digging material, with a new pair of containers presented every 2 min during a 20 min session. Multisensory cues distinguished the rewarded vs. non-rewarded containers. We hypothesized that, if rats became bored by sensory monotony, rats in a monotonous version of the scenario would show more arousal-seeking (e.g. exit-directed behaviour, jumping) and drowsy behaviour (e.g. standing still, yawning, task disengagement) than in a varied version. In the Monotony treatment, the digging material, reward flavour, and features of the cues remained constant in each presentation, whereas these changed throughout the Variety treatment. Behaviour was observed blind to treatment in a randomised order. Monotony significantly increased exit-directed behaviour compared with Variety, but no other treatment effects reached significance. Possible reasons for the relative lack of findings are discussed, including suggestions for future research. Here, sensory monotony during the task did not induce the full range of behaviours characterizing boredom, but it is of interest that it did increase exit-directed behaviour.